PERSEPSI MASYARAKAT TERHADAP RELEVANSI PENDIDIKAN AGAMA ISLAM DALAM MENGHADAPI ARUS GLOBALISASI - Achmad Samsul Arifin (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to identify how the community of Burangkeng Village, Setu District, Bekasi Regency perceives the relevance of Islamic Religious Education (PAI) amid the increasingly powerful currents of globalization. The phenomenon of globalization has brought significant impacts, including the development of information technology, economic integration, and the influx of foreign cultures that frequently conflict with Islamic principles. The method used in this study is descriptive quantitative with a survey involving 180 respondents selected through purposive sampling from parents, educators, students, community leaders, and workers. The data collection instrument was a questionnaire using a 5-point Likert scale covering four aspects of relevance: moral-character, cultural, digital-technology, and economic-career capability. Data analysis was conducted using descriptive statistics (percentages, mean, and standard deviation). The findings reveal that the community's overall perception is positive and high (mean 4.18). The moral-character aspect received the highest score (mean 4.45), indicating that PAI serves as the primary shield against materialism, moral decline, and the negative impacts of social media. However, the digital-technology and economic-career capability dimensions tend to be moderate (mean 3.72), suggesting the need for curriculum updates to be more responsive to digital literacy and 21st-century skills without neglecting Islamic values. This study recommends the development of an integrative PAI model that unites traditional values with contemporary approaches in line with the character of the suburban community of Bekasi.